PROPORSIONALITAS WARTAWAN TELEVISI LOKAL DI BATU TV - Aryo Prakoso Wibowo (Universitas Merdeka Malang, 2018)
Abstract This study aims to determine the extent to which the professionalism of TV journalists to process information to become a debate of opinion for the local community about local phenomena. The process of producing news is important to provide good news content to the public. The good news is presented by journalists who understand and adhere to the journalist's code of ethics. Because journalists are professionals who work based on rules or code of ethics journalism as an operational handle to maintain public confidence, uphold integrity and professionalism. The performance of journalists must uphold the code of ethics of television journalists, among other things